Simulation Analysis of Inverting Marine Vertical Deflection Using Spaceborne GNSS-R Interferometric Altimetry - Lichang Duan; Junming Xia; Weihua Bai; Zhenhe Zhai; Feixiong Huang; Cong Yin; Yueqiang Sun; Qifei Du; Dongwei Wang; Xianyi Wang; Yixuan Sun; Shengyu Kang; et al. (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Global marine vertical deflection is essential for understanding Earth's internal mass and density distribution and improving the long-term inertial navigation accuracy of underwater vehicles. Spaceborne global navigation satellite system reflectometry (GNSS-R) interferometric altimetry, with its advantages of low-cost, rapid global coverage, and revisiting capability, shows promise as new data for compensating the radar altimeters. In this study, we present the first simulation of spaceborne GNSS-R interferometric altimetry data based on FY-3E GNSS-R trajectory and evaluate its potential for inverting global marine vertical deflection. Our results showed that, in the operational scenario (with a spatial resolution of 10 km and an altimetry accuracy of 14.68 cm), the total accuracy of marine vertical deflection for global 2.5′, 5′, and 20′ grids, obtained from ten years of simulation data, was 4.998″, 1.268″, and 0.1″, respectively. Furthermore, we observed that, when the average global revisit times reached approximately 90 times and 6 times, the total accuracy of marine vertical deflection for global 5′ and 20′ grids was below 1″. As the GNSS-R detection on the FY-3E satellite covers 90% of the global sea area in 20′ grids within 23 days, with an average revisit time of 7.3, spaceborne GNSS-R interferometric altimetry has the potential to invert the high-precision time-variable gravity field with a 20′ resolution, thus compensating for the lower resolution provided by satellite gravimetry.